ON IMPROVING THE COMPETITIVENESS OF TOURISM ORGANIZATIONS IN MODERN CONDITIONS - V. Zhuravel (Вестник Северо-Кавказского федерального университета)
In the framework of this study, the main directions of improving the competitiveness of the tourism organization in order to conquer the market of services, improve the efficiency of the company in modern economic conditions. It is concluded that modern activities in the field of tourism should be based on industry characteristics. As a result, it is important to highlight a number of common features characteristic of tourism management: the priority of the desires of end users in the planning of tourism activities; novelty/ uniqueness of tourism services; great importance of marketing in the tourism industry.